Square-Wave Pulse Deposition of Pt Nanoparticles for Ethanol Electrooxidation - Syafei, Devi Indrawati; Syafei, Hilman (Chemistry and Materials, 2024)
Platinum (Pt) is often used as an electrocatalyst in the electrooxidation of ethanol. There have been many attempts to improve the catalytic properties of platinum-based catalysts to achieve satisfactory results. The solutions are manipulating the size and shape of Pt. In this study, Pt will be deposited using the square wave pulse deposition method at upper potential variations. The Pt samples were characterized by scanning electron microscopy (SEM), X-ray diffraction, energy dispersive X-ray, and electrochemical impedance spectroscopy. The results of SEM show that the morphology of Pt at potentials of 0.3 V, 0.5 V, and 1.0 V produces a dendritic nanothorn morphology, while 1.25 V and 1.50 V produce a nanoleaf morphology. The lowest charge transfer resistance value is at Pt1.0V with the smallest size. The highest yield of ethanol electrooxidation was at Pt1.0V reaching 8.82 mA/cm2.